Ø£ÙˆØ§Ù…Ø± ÙÙŠ Ø³ÙˆØ±Ø© Ø§Ù„Ù†Ø³Ø§Ø¡ Ø§Ù„Ù…ØªØ¹Ù„Ù‚Ø© Ø¨Ø£ØÙƒØ§Ù… Ø§Ù„Ø£Ø³Ø±Ø©; Ø¯Ø±Ø§Ø³Ø© ØªØ·Ø¨ÙŠÙ‚ÙŠØ© - Awal Rifai; Usamah Maming (Ø§Ù„Ø¨ØµÙŠØ±Ø©: Ù…Ø¬Ù„Ø© Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ©, 2020)
Surah An-Nisa is one of the longest madaniah surah, and is one full of provisions of sharia laws that govern all matters both internal and external ones for Muslims. Among the prominence of this noble surah is that it tells a lot about important things related to women, household, family, country, and social life. In this surah, there are commands and prohibitions in various matters. The purpose of this study was to extract imperative sentences related to family life and then briefly identify the rules that became the base for these commands. The researcher employed an inductive and analytical approach by extrapolating Surah Al-Nisa, taking imperative sentences related to family life, and explaining the law which is concluded from it. Researcher finds, among the most important of the most important ones are as follows: understanding the meaning of al-amr (command) which is a request to do something in the form of superiority. There are two types of amr: direct and indirect. The number of amr related to the family in the surah is seventeen.